KARAKTERISTIK SOSIODEMOGRAFI PESERTA PROGRAM PENDIDIKAN UNTUK MENINGKATKAN KOMPETENSI KADER DI BANJARNEGARA JAWA TENGAH - Dewie Sulistyorini (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2024)
Background Indonesia still has a high maternal mortality rate compared to other Southeast Asian countries. In Banjarnegara Regency, the ratio of pregnant women to midwives falls far behind short of than the target set by the Indonesian Ministry of Health for 2025. Therefore, the need for health cadres, who assist midwives within the health system, is imperative to support pregnant women. To accomplish health cadre’s role efficiently, it is needed to enhance their competency in identifying risk factors and referring high-risk pregnant women to midwives. Purpose This study aimed to improve the competency of health cadres through the educational program. Methods A cluster non-randomized controlled trial was conducted, from November 2023 to February 2024. Results The age was significantly younger in the CG (p=0.017). Moreover, their work experience was significantly longer in the IG (p=0.044). In both groups, more than 50% of participants had education levels in senior high school, and most of them were married (96.9%) and had children (96.2%) Conclusion The age of health cadre affects to their competencies. We recommend recruiting health cadres who are young to maintain their competence in monitoring high-risk pregnant women.